Database systems : design, implementation and management - Rob, Peter; Coronel, Carlos
Summary: Revised edition of a textbook that provides a comprehensive introduction to database management systems. Part 1 contains six chapters on database design concepts. Part 2 presents a detailed, real-world design case, in which the concepts of Part 1 are put to work. Part 3 covers database administration, transaction management, distributed databases, object orientation and the extended relational database, and client/server computing. Finally, Part 4 looks back at older database models. Includes a detailed glossary.